Genetic mapping of northern corn leaf blight-resistant quantitative trait loci in maize. Issue 31 (31st July 2020) - Xia, Haifeng; Gao, Wei; Qu, Jing; Dai, Liqiang; Gao, Yan; Lu, Shi; Zhang, Mo; Wang, Piwu; Wang, Tianyu
Abstract : Abstract: Northern corn leaf blight (NCLB), a corn disease infected by Exserohilum turcicum, can cause loss of harvest and economy. Identification or evaluation of NCLB-resistant quantitative trait loci (QTL) and genes could improve maize breeds. This study aimed to identify novel QTLs for NCLB-resistance. Two maize strains (BB and BC) were utilized to generate B73 × B97 and B73 × CML322 and constructed the genetic linkage using high-throughput single nucleotide polymorphism (SNP) linkage map analysis of 170 (BB) and 163(BC) recombinant inbred line (RIL) genomic DNA samples. NCLB-resistant QTL was associated with phenotypic data from the field trial of 170 BB and 163 BC strains over two years using these 1100 SNPs to identify high-density NCLB-resistant QTLs. In BB, QTL of the NCLB resistance was on chromosome 1 and 3 (LOD scores between 2.74 and 5.44); in BC, QTL of NCLB resistance was on chromosome 1, 2, 4, 8, and 9 (LOD scores between 2.52 and 8.53). A number of genes or genetic information related to NCLB resistance in both BB and BC were identified with the maximum number of genes/NCLB resistance-related QTL on chromosome 3 for BB and on chromosome 1 for BC. This study successfully mapped and identified NCLB-resistant QTL and genes for these 2 different maize strains, which provides insightful information for future study of NCLB-resistance and selection of NCLB-resistant maize variants. Abstract : Supplemental Digital Content is available in the text